ANALISIS WILLINGNESS TO PAY BERAS ORGANIK AROMATIK “BOTANIK” GAPOKTAN AL-BAROKAH DI KABUPATEN BONDOWOSO - Elrey All Habib; Ebban Bagus Kuntadi (University of Jember, 2020)
The development of organic rice in Bondowoso has high growth. The superiority of the product makes the selling value of the product not cheap when compared to other rice products. The objectives of the study are (1) to determine the characteristics of aromatic organic rice consumers in Al-Barokah Gapoktan in Bondowoso, (2) the price of consumers willing to pay for aromatic organic rice, (3) the factors that influence consumers' WTP value of aromatic organic rice. Method of determining the area using a purposive method in the Botanic shop. Sampling using incidental sampling technique with a total of 45 respondents. The results show: (1) the characteristics of Botanic aromatic organic rice consumers are the majority of middle-aged men who have a tertiary education level with non-PNS jobs and have an income of> 3,000,000 000 4,000,000 and already have a total dependents of family members of 3 people, (2) willingness to pay Botanic aromatic organic rice products is Rp. 18,133 per 1kg higher when compared to prevailing prices in the shop which is Rp. 17,500 so that means there is a consumer surplus of Rp. 633, and (3) Factors factors that significantly affected the willingness to pay for organic rice in were age, education level, type of work, healthy food concern, and income. Keywords: Organic Rice, Consumer Characteristics, Willingness to Pay